Electrokinetics and Electrohydrodynamics in Microsystems - Ramos, Antonio; SpringerLink (Online service). (Vienna Springer Vienna Imprint: Springer, 2011)
Among the most promising techniques to handle small objects at the micrometer scale are those that employ electrical forces, which have the advantages of voltage-based control and dominance over other forces. The book provides a state-of-the-art knowledge on both theoretical and applied aspects of the electrical manipulation of colloidal particles and fluids in microsystems and covers the folllowing topics: dielectrophoresis, electrowetting, electrohydrodynamics in microsystems, and electrokinetics of fluids and particles. The book is addressed to doctoral students, young or senior researchers, chemical engineers and/or biotechnologists with an interest in microfluidics, alb-on-chip or MEMS.
Keywords: Electronic books; Engineering; Biotechnology; Chemical engineering; Nanotechnology and Microengineering; Nanoscale Science and Technology; Industrial Chemistry/Chemical Engineering